2017
DOI: 10.18203/2320-6012.ijrms20172486
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about anesthesia and the role of anesthesiologists among Jeddah citizens

Abstract: Background: The anesthesiologist has a vital role in the operating theatres. Awareness of the role of the anesthesiologist and the types of anesthesia is essential for every person. This study was made to estimate how much information the general population have about the anesthesiologist and the different types of anesthesia.Methods: This research was a cross sectional non-interventional study. The research team conducted a questionnaire in which each participant in the study was interviewed by the research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The current questionnaire was adopted from previous studies. As having significant internal validity reported by previous research [3,10]. The questionnaire also had a significant external validity as being applicable to a vast and diverse population, in light of previous literature [11][12].…”
Section: Sampling Technique (With Inclusion and Exclusion Criteria)mentioning
confidence: 56%
See 2 more Smart Citations
“…The current questionnaire was adopted from previous studies. As having significant internal validity reported by previous research [3,10]. The questionnaire also had a significant external validity as being applicable to a vast and diverse population, in light of previous literature [11][12].…”
Section: Sampling Technique (With Inclusion and Exclusion Criteria)mentioning
confidence: 56%
“…For many years, anesthesiology was considered a behind-the-scenes specialty. It was publicly introduced in 1846 [3], and from that time until now, anesthesiologists have played an important and sensitive role in pain clinics, operating rooms, and ICUs [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in Saudi Arabia reflected the ignorance of the public about the function of anesthesiologists, a lack of perception regarding anesthetic procedures during surgery, and the role of the anesthesiologist in monitoring resuscitation and postoperative analgesia [ 4 ]. A more recent study in Saudi Arabia revealed a relative lack of information about the role of the anesthesiologist both intraoperatively and postoperatively [ 5 ]. These elements could increase preoperative anxiety and lower post-anesthesia patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the anesthetic rooms are designed to be separate from the operating theaters; thus, allowing the parents to attend induction of anesthesia with their child and prevent pediatric patients from seeing and hearing the surgical equipment setup, therefore reducing their anxiety. [ 19 , 20 ] This is different to practice in Saudi Arabia (KSA) in which the induction of anesthesia occurs inside the operating theater,[ 21 ] which might produce too complex of a working environment for parents to be present. [ 14 ] In comparison to pediatric anesthetists in the UK, anesthetists in the US did not prefer PPIA in their practice, indicating a cultural difference.…”
Section: Introductionmentioning
confidence: 99%